Ribosomal Protein SA-Positive Neutrophil Elicits Stronger Phagocytosis and Neutrophil Extracellular Trap Formation and Subdues Pro-Inflammatory Cytokine Secretion Against Streptococcus suis Serotype 2 Infection - Sun, Qiang; Li, Na; Jia, Li; Guo, Wenfei; Jiang, Hexiang; Liu, Baijun; Bao, Chuntong; Liu, Mengmeng; Huang, Jing; Lei, Liancheng (Frontiers in Immunology, 2021)
Streptococcus suis serotype 2 (SS2), an important zoonotic pathogen that causes septicemia, arthritis, and irreversible meningitis in pigs and humans, can be transmitted to humans from pigs. S. suis causes huge economic losses to the swine industry and poses a serious threat to public health. Previously, we found that the brain tissues of mice with SS2-induced meningitis showed disrupted structural integrity and significantly enhanced polymorphonuclear neutrophil (PMN) infiltration. We showed that the brain tissues of SS2-infected mice had increased ribosomal protein SA (RPSA)-positive PMN counts. However, the inflammatory responses of RPSA+ PMNs to SS2 and their effects on the blood-brain barrier (BBB) remain unclear. Therefore, in studying the pathogenesis of SS2-induced meningitis, it is essential that we explore the functions of RPSA+ PMNs and their effects on the BBB. Herein, using flow cytometry and immunofluorescence microscopy analyses, we found that RPSA expression enhances PMN-induced phagocytosis and PMN-induced formation of neutrophil extracellular traps (NETs), which facilitate further elimination of bacteria. PMN surface expression of RPSA also alleviates local inflammation and tissue injuries by inhibiting secretion of the pro-inflammatory cytokines, TNF-α and IL-6. Moreover, the single-cell BBB model showed that RPSA disrupts BBB integrity by downregulating expression of tight junction-associated membrane proteins on PMNs. Taken together, our data suggest that PMN-surface expression of RPSA is a double-edged sword. RPSA+ PMN owns a stronger ability of bacterial cleaning and weakens inflammatory cytokines release which are useful to anti-infection, but does hurt BBB. Partly, Partly, RPSA+ PMN may be extremely useful to control the infection as a therapeutic cellular population, following novel insights into the special PMN population.